The Non-invasive carotid vascular assessment in our setting - Esperón, Alejandro; López Chapuis, Daniel; Gómez Fossati, Carlos (Cirugía del Uruguay, 1996)
The revolutionary progress of non-invasive methods of eva!uation of atheromas of the carotid bifurcation has great!y changed the a/gorythm far the study of these patients. As these are methods that depend on the technician, it is of utmost importance to know the degree of confidence that each study may have in each specific environmen